Policy Implementation of Educational Quality Improvement Based on National Education Standard - Lydia, Lydia; Fitria, Happy; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2020)
The objective of the study was to know the implementation of policies to improve the quality of education at SMP Negeri 2 Sekayu towards the National Education Standards. This study uses a qualitative method. Subjects in this study were school principals, Deputy for Facilities and Infrastructure, Student Associates, Teachers, and Students. Data collection was carried out by interview, observation, and documentation. Data were analyzed by data reduction, data presentation, and conculsion drawing. From the research results it can be concluded that the quality of education at SMP Negeri 2 Sekayu has met the requirements as a school with very good quality with the accreditation it has, namely the predicate